A distributed fuzzy logic controller for a prosthetic hand / Mohd Yazed Ahmad - Mohd Yazed, Ahmad (2006)
A Fuzzy Logic with distributed control monitoring (D S) sy tern i implemented to control multiple degree-of-freedom (DOF) prosthetic fingers. Ther are four fingers with 3-DOF and a thumb with 4-DOF. Five identical microcontrollers programmed with Fuzzy Logic ontroller (FLC) and a ystem Handler are employed to control and monitor the fingers and the thumb to replicate the desired hand action of the grasp, the key pinch, the pulp to pulp pinch, the tripod pinch, and the open hand. Each finger is equipp d with position sensors at the pi ot joints and a tactile-pressure sensor at the fingertip. The finger mo ements are programmed to follow given set points and stopped ,. h ne er an obstacle is encountered and the pressure of the tactile sensor exceeds a specified limit. This allows the fingers and thumb to wrap round an object without crushing it. DC motors with reduced gear heads are used as actuators and they are dri en by H-Bridge sv itches. Input signals to the switches in the form of Pulse Width Modulation (PWM) and direction signals are generated by the microcontroller . The signal r present control action of the FLC. Membership functions of the FLC were tuned and the rule \ ere formed to obtain the desired response. Distributed control is implemented by conn cting all finger microcontrollers to a main microcontroller that can b integrated with the Brain omputer Interface. The o erall system was constructed and te ted successfully to control the prosthetic hand.